Factors influence consumer behavior on spending pattern at Al-Ikhsan sport sdn bhd : case study at Jusco Aeon Tebrau, Johor / Nursyuhada Mustafha Kamaruddin - Mustafha Kamaruddin, Nursyuhada (2013)
Sports are getting a new highlight in world nowadays. People learn that leading a healthy lifestyle give will more than they expecting. People like to do exercise in a very fashionable way. So, as an entrepreneur, Ali bin Hassan come out with an idea to join the sports retailer business. Provide a fashiobale sportswear yet comfortability included.From this statement tting a new highlight ithis paper will research about factor influence consumer behavior on spending pattern at aL-ikhsaN Sports Sdn Bhd, where case study at Jusco Aeon Tebrau. The problem statement of this research can be developed because the objectives of this study are to determine the relationship between location, price, customer services and quality of product to consumer behavior of aL-ikhsaN Sport Sdn Bhd. Research methodology using in this study is quantitative study, and this study was conducted to aL-ikhsaN Jusco Aeon Tebrau costumer. A survey was conducted through distributing questionnaires to customer from different background. A total of 110 self-administered questionnaires were distributed. Using quantitative analysis, the data was computed and analyzed by using SPSS program.